Coping with COVID: Preparing prescribers during the pandemic. Issue 5 (22nd December 2021) - Ferner, Robin E.; Mason, Julie; Vallance, Hannah K.; Choudhary, Tanvi; Marriott, John F.; Coleman, Jamie J.; Pontefract, Sarah K.
Abstract : In response to the COVID‐19 pandemic, Health Education England (HEE) and the University of Birmingham provided National Health Service (NHS) staff free access to SCRIPT, a national eLearning programme for safer prescribing and therapeutics. The eLearning was particularly for those returning to work or being redeployed. In the year March 2020‐21, 3412 users registered to access portfolios and opened an aggregate of 17 198 modules. Each user completed a median of 2 (range 1‐50, interquartile range [IQR] 1‐7) assessed learning modules. Marks improved from pre‐test to post‐test by a median of 2 (IQR 0‐3) marks out of 10. The most frequently selected modules were Adherence and Concordance (1109 users), Fluids (981 users) and Diabetic Emergencies (818 users). A total of 878 users accessed the unassessed COVID‐19 module. The SCRIPT modules provided standardised education in core principles relating to prescribing and therapeutics, and were used by professionals from many healthcare disciplines.